INTEGRATION OF SCIENCE IN THE PERSPECTIVE OF ISLAMIC EDUCATION PHILOSOPHY - Kenny Agusto Arie Wibowo (PT Rahis Cendekia Indonesia, 2023)
Knowledge in general is everything that is known to humans, in this case what is known to humans can be interpreted as a human view. The human view is something that can be said to be the beginning of knowledge, because one's view can be an analysis that ultimately results in knowledge. But in this case, there are still many of us who are still wrong in using the knowledge we have for things that are not good. With regard to this knowledge, there are still many of us who neglect their knowledge only for their own benefit. This is a common concern, because wild knowledge will produce wild knowledge as well. For that we need an integration between knowledge and the resulting science, because the integration of science will produce a work that enlightens not misleads all humans. Based on this, the study of philosophy examines this knowledge based on epistemological studies. Because with this study we can interpret a knowledge that is integrated with science in order to produce a good science.